Elphie : a Wicked childhood - Maguire, Gregory (William Morrow, an imprint of HarperCollinsPublishers, 2024)
"What happened to young Elphaba before her witchy powers took hold in Wicked? Almost 30 years after publication of the original novel, for the first time Gregory Maguire reveals the story of prickly young Elphie, the future Wicked Witch of the West"--